Hubungan al-Asma’ al-Husna Dengan al-Sidq Perspektif al-Ghazali Berdasarkan al-Maqsad al-Asna: Relationship between al-Asma’ al-Husna and al-Sidq according To al-Ghazali’s Perspective in al-Maqsad al-Asna - Shuhari, Mohd Hasrul; Hamat, Mohd Fauzi; Engku Wok Zin, Engku Ibrahim; Wahab, Muhammad Rashidi; Rozali, Muhammad Hafizi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
Understanding of al-Asma’ al-Husna among Muslims is something that Islam advocates as embodied in the Qur’an and the Sunnah of the Prophet (p.b.u.h.). All the instructions from Allah SWT and the Messenger of Allah (p.b.u.h.) are certainly privileges to Muslims. Among his privileges is the impulse to inculcate al-sidq (trueness) in a Muslim individual. This paper aims to explain the concept and method of understanding al-Asma’ al-Husna based on al-Ghazali’s thought (d. 505). The relationship between the understanding of al-Asma’ al-Husna and the characteristics of al-sidq that can be formed in Muslim individuals will also be explained. This paper uses text analysis methodology focused on al-Ghazali’s al-Maqsad al-Asna fi Sharh Asma’ Allah al-Husna. This paper concludes that a correct understanding of al-Asma’ al-Husna will help and encourage a Muslim individual to possess al-sidq as there is a significant relationship between al-Asma’ al-Husna and understanding of al-sidq.